True World Income Distribution, 1988 and 1993 : First Calculations, Based on Household Surveys Alone - Milanović, Branko, 1953- 1953- (The World Bank, 1999)
Inequality in world income is very high, according to household surveys, more because of differences between mean country incomes than because of inequality within countries. World inequality increased between 1988 and 1993, driven by slower growth in rural per capita incomes in populous Asian countries (Bangladesh, China, and India) than in large, rich OECD countries, and by increasing income differences between urban China on the one hand and rural China and rural India on the other. - Milanovic derives the distribution of individuals' income or expenditures for two years, 1988 and 1993. His is the first paper to calculate world distribution for individuals based entirely on data from household surveys. The data, from 91 countries, are adjusted for differences in purchasing power parity between the countries. Measured by the Gini index, inequality increased from an already high 63 in 1988 to 66 in 1993. This increase was driven more by rising differences in mean incomes between countries than by rising inequalities within countries. Contributing most to the inequality were rising urban-rural differences in China and the slower growth of rural purchasing-power-adjusted incomes in South Asia than in several large developed market economies. This paper - a product of Poverty and Human Resources, Development Research Group - is part of a larger effort in the group to study inequality and poverty in the world. Also published in The Economic Journal, January 2002 pp. 51-92 The author may be contacted at bmilanovic@worldbank.org